Intracellular Cholesterol Synthesis and Transport - Shi, Qingyang; Chen, Jiahuan; Zou, Xiaodong; Tang, Xiaochun (Frontiers in Cell and Developmental Biology, 2022)
Cholesterol homeostasis is related to multiple diseases in humans, including cardiovascular disease, cancer, and neurodegenerative and hepatic diseases. The cholesterol levels in cells are balanced dynamically by uptake, biosynthesis, transport, distribution, esterification, and export. In this review, we focus on de novo cholesterol synthesis, cholesterol synthesis regulation, and intracellular cholesterol trafficking. In addition, the progression of lipid transfer proteins (LTPs) at multiple contact sites between organelles is considered.